Islam and Civil Society in Southeast Asia - Siddique, Sharon; Mitsuo, Nakamura; Bajunid, Omar Farouk (Book collections on Project MUSE., 2001)
The Islamic world, often regarded as an anathema to civil society, in fact has rich traditions of associational life pursuing "common good". These religious resources have been reinterpreted for the enhancement of civic virtues and participatory politics in contemporary context, that is, democratization. Such pioneering efforts have been clearly observable in Muslim Southeast Asia. In November 1999, the Sasakawa Peace Foundation invited ten Muslim activists and scholars from the region to Japan for exchanging views and experiences among themselves and with Japanese participants. Here their papers and discussions are compiled into a book, Islam and Civil Society in Southeast Asia.